PIDATO POLITIK DI INDONESIA: SEBUAH KAJIAN WACANA KRITIS - Diah Ikawati Ayuningtias (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
Language is not neutral, but it is depending on who is using thelanguage. Research on the use of language in political speeches isinteresting and important thing to do with the following objectives: ( 1 ) to describe the use of elements of language in relation to ideology and role played by political parties in Indonesia, ( 2 ) to identify power relations which was formed by leaders of political parties in Indonesia through their political speeches.The results showed that the elements of the language used in the speech demonstrated the role in term of textual analysis involving the use of pronouns , transitivity, modalities to demonstrate its power level, aspects, coherence, lexical analysi about the use of certain terms that are closely related to the life social. In terms of discourse practices, especially intertextuality, it is also used the phrase referring to a slogan or philosophy in Indonesia and the familiar to the public. In terms of social practice, in delivering his speech, the party leaders are motivated by social andpolitical conditions exist. For power relations constructed in their speeches, the party leaders do not always constant in building its power. It depends on the intent and purpose of what is delivered. Sometimes power is built on a superior position, but on the other hand it is inferior and sometimes also becoming equal. Given that language is not neutral then, the power relations also become liquid.